2010
DOI: 10.1111/j.1530-0277.2010.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

The Obsessive Compulsive Drinking Scale Is a Valid Measure of Alcohol Craving in Young Adults

Abstract: Using the 4-factor structure, the OCDS is a valid measure of alcohol craving in young adult populations. In this nonclinical set of students, the OCDS classified nonproblem drinkers well but not problem drinkers. Studies need to further examine the utility of the OCDS in young people with alcohol misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…The results of different CFA models are shown in Table 3 . Comparing to other models in previous studies, our new 3-factor model from EFA showed good fitness to the Chinese OCDS (CFI was 0.87, which nearly achieved optimal fitness as 0.90), and the identified factors were consistent with some models from previous studies, such as Connor's 4-factor model ( 12 ) and Bohn's 4-factor model ( 7 ). Original items 3, 4, 9, and 10 were fit for one of the four factors identified by Connor et al, while original items 5, 6, 11, 12, 13, and 14 were fit for another one of the four factors identified by Bohn et al…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The results of different CFA models are shown in Table 3 . Comparing to other models in previous studies, our new 3-factor model from EFA showed good fitness to the Chinese OCDS (CFI was 0.87, which nearly achieved optimal fitness as 0.90), and the identified factors were consistent with some models from previous studies, such as Connor's 4-factor model ( 12 ) and Bohn's 4-factor model ( 7 ). Original items 3, 4, 9, and 10 were fit for one of the four factors identified by Connor et al, while original items 5, 6, 11, 12, 13, and 14 were fit for another one of the four factors identified by Bohn et al…”
Section: Resultssupporting
confidence: 80%
“…We found that the three-factor model could wellexplain the structure of the scale (three factors accounting for 68% of the variation). Both our new model and Connor's model (12) indicated that original items 3, 4, 9, and 10 in OCDS reflected the structure measuring interference from alcohol, while both our new model and Bohn's model (7) suggested original items 5, 6, 11, 12, 13, and 14 in OCDS reflected the structure measuring resistance to alcohol consumption. In our model, items 1, 2, 7, and 8 were grouped into the same factor, which reflected obsessions and compulsions for alcohol.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The Obsessive and Compulsive Drinking Scale (OCDS) (Ansseau et al, 2000;Connor et al, 2010), is a 14-item self-report instrument with a 5-point response scale (0 to 4) that quantifies both obsessions and compulsions related to drinking. Higher scores indicate more obsessive thoughts or compulsive behaviors regarding alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…This is in spite of common reporting of urges and desires for drinking used in the everyday lexicon of non-dependent drinkers. There is some empirical evidence that craving is experienced by young, recreational drinkers (Connor, Feeney, Jack, & Young 2010;Love, James, & Willner, 1998;McEvoy, Stritzke, French, Lang, & Ketterman, 2004). For example, in a sample of college students (n = 309), Connor, et al (2010) found that a widely used measure of alcohol craving, the Obsessive Compulsive Drinking Scale (OCDS, Anton, Moak, & Latham, 1995), predicted approximately half of the variance in Alcohol Use Disorder Identification Test scores (AUDIT, Saunders, Aasland, Babor, De La Fuente, & Grant, 1993) and a quarter of the variance in average consumption per drinking occasion.…”
Section: Introductionmentioning
confidence: 99%